Confocal and Electron Microscopic Structure of the Cornea from Three Species of Penguin - Peter W. Hadden; Akilesh Gokul; Satya Amirapu; Ratish Kurian; Charles N. J. McGhee; Jie Zhang (Vision, 2023)
Corneal confocal microscopy has not previously been performed in penguins, despite recognition of its unusually flat shape. To identify features that the penguin shares with other birds and or mammals and those specific to penguins, we undertook confocal microscopic examination of two little (Eudyptula minor), four gentoo (Pygoscelis papua) and five king (Aptenodytes patagonicus) penguin corneas. Transmission electron microscopy was performed on one gentoo and one king penguin, for finer details. Features shared with other higher vertebrates included a five-layered cornea and a similar limbus. Typically avian were a lower density of stromal cells, a more regular arrangement of collagen bands and an absent basal nerve plexus. Features unique to penguins included a flattened superficial epithelium (king penguin), stromal myofibroblasts (all) and an irregular endothelium (little penguin). Other features uniquely identified by confocal microscopy in birds include epithelial and stromal nerves, guttata and stromal imprints on Descemet’s membrane. Transmission electron microscopy identified a lack of wing cells (king penguin), greater posterior collagen lamellae thickness (gentoo penguin) and significantly less interlacing of collagen lamellae in the central cornea (king and gentoo). Most of these unique features are yet to be explained, but some could be adaptations to diving.